The origin of athermal training in polycrystalline metallic exchange bias thin films - Kaeswurm, Barbara; O'Grady, K. (Applied Physics Letters, 2011)
The phenomenon of training in exchange bias systems has no clear and unambiguous explanation. It is known that the training effect consists of an athermal and a thermal component where the latter derives from the well understood thermal instability in the bulk of the antiferromagnetic (AF) grains. In this work, we report on a study of the magnetic properties of a tri-layer system consisting of F/AF/F where reversal of the individual ferromagnetic (F) layers shows that the athermal training effect derives solely from the interface spin configuration and not from the bulk of the AF grains. We propose a model whereby the origin of the training derives from the degree of order in interfacial spin clusters which lie in a thermo-remanent state after the AF is set and whose order is disrupted by the application of a reverse field resulting in a reduced coercivity and the characteristic change in the loop shape. (C) 2011 American Institute of Physics. [doi:10.1063/1.3661172]
Keywords: antiferromagnetism; coercive force; ferromagnetism; magnetic multilayers; magnetic thin films; metallic thin films; remanence; spin systems